Synthesis, characterization, and thermal investigation of copper(II), nickel(II), cobalt(II), and zinc(II) complexes with 5-benzoyl-1-(phenylmethylenamino)-4-phenyl-1H-pyrimidine-2-thione - Sönmez, M; Sekerci, M (Marcel Dekker Inc, 2003)
Cu(II), Ni(II), Co(II) and Zn(II) complexes of 5-benzoyl-1-(phenylmethylenamino)-4-phenyl-1H-pyrimidine-2-thione were prepared. These complexes have been characterized by elemental analyses, IR, NMR and UV-Vis spectra. Spectral studies, magnetic moment and molar conductivity measurements were performed on these compounds. All of the complexes are non-electrolytes. The metal complexes are proposed to have an octahedral Structure. Thermal Studies of the complexes are also reported.
Keywords: pyrimidine-2-thione; metal complexes